(untitled) (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2017)
This article is the product of being asked to reflect on the practice of counselling psychology as an interpretative practice. The author illustrates how her work as a student clinician is nothing but interpretive, and argues that interpretation is a necessary means of understanding and moving with one’s client throughout the therapy process.